PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DEDICADA A LA PRODUCCIÓN Y COMERCIALIZACIÓN DE JACA (JACKFRUIT) DESHIDRATADA EN EL CANTÓN HUAQUILLAS, PROVINCIA DE EL ORO - Naula Vacacela, Mishel Lisbeth (2019)
The main objective of the current work was to develop a study to determine the feasibility of implementing a company dedicated to the production and commercialization of dehydrated jackfruit in Huaquillas canton, at Oro Province, which will serve as a guide to generate a new business project that provides consumers with products that are healthy, natural and contribute to enrich the daily diet of the general population. For which the application of deductive, statistical and analytical methods was determined. In addition, data collection techniques such as survey and direct observation were designed. To determine the feasibility of the project, it began with the market study with a sample of 374 families, it was determined that the effective demand is 198,584 potential customers, as for the offer is 91,930 people who buy dehydrated fruit. Regarding unmet demand there are 106,654 potential customers. Through the technical study it was determined that the installed capacity of the project will be 147,825 annual production in pounds, while the used capacity will be 35,100 annual production in pounds, the company will be located in the downtown of Huaquillas canton, on Esmeraldas and Hualtaco avenues. In the productive process, it demands the use of adequate machines and equipment, physical distribution, the process diagrams, the establishment of the company and other items that make up the start-up of the business were established. In the financial study it was established that the project reaches an initial investment of 5 $ 47.562,92 dollars, fixed assets with a total of $ 32.306,00; deferred assets $ 1.858,00 dollars and a working capital of $ 13,398.92. the financing will be 58% of the capital from the partners and 42% financed by BanEcuador. Finally, the financial evaluation determined that the Net Present Value (NPV) which obtained a positive result at $ 61.229,78 the Internal Rate of Return (IRR) is 50.50%, the Cost Benefit Ratio (CBR) was obtained for each invested dollar you get 0.24 cents of return, the Period of Recovery of Capital (PRC) was determined that the investment is recovered in 1 year 11 months and 16 days, finally the Sensitivity Analysis with increase in costs is of 11.03% and a decrease in income of 8.98%, which indicates that it is feasible to start the project, which conclusions and recommendations determine it.